Anion‐Exchange Driven Phase Transition in CsPbI3 Nanowires for Fabricating Epitaxial Perovskite Heterojunctions. Issue 19 (11th April 2022) - Li, Jing; Xu, Jiao; Bao, Yanan; Li, Jianliang; Wang, Hengshan; He, Chengyu; An, Meiqi; Tang, Huayi; Sun, Zhiguang; Fang, Yurui; Liang, Shuang; Yang, Yiming
Abstract: Anion‐exchange in halide perovskites provides a unique pathway of bandgap engineering for fabricating heterojunctions in low‐cost photovoltaics and optoelectronics. However, it remains challenging to achieve robust and sharp perovskite heterojunctions, due to the spontaneous anion interdiffusion across the heterojunction in 3D perovskites. Here, it is shown that the anionic behavior in 1D perovskites is fundamentally different, that the anion exchange can readily drive an indirect‐to‐direct bandgap phase transition in CsPbI3 nanowires (NWs) and greatly lower the phase transition temperature. In addition, the heterojunction created by phase transition is epitaxial in nature, and its chemical composition can be precisely controlled upon postannealing. Further study of the phase transition dynamics reveals a threshold‐dominating anion exchange mechanism in these 1D NWs rather than the gradient‐dominating mechanism in 3D systems. The results provide important insights into the ionic behavior in halide perovskites, which is beneficial for applications in solar cells, light‐emitting diodes (LEDs), and other semiconductor devices. Abstract : The solid‐state anion exchange is conducted in Y‐CsPbI3 /CsPbBr3 nanowire crossbar structures, driving an indirect‐to‐direct bandgap phase transition in Y‐CsPbI3 nanowires. The heterojunction created by phase transition is epitaxial, with sharp interface and excellent thermal stability. A threshold‐dominating anion exchange mechanism is proposed in these 1D nanowires, fundamentally different from the gradient‐domination mechanism in 3D perovskites.